2016
DOI: 10.5194/acp-16-9505-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence of large aspherical <i>β</i>-NAT particles involved in denitrification in the December 2011 Arctic stratosphere

Abstract: Abstract. We analyze polar stratospheric cloud (PSC) signatures in airborne MIPAS-STR (Michelson Interferometer for Passive Atmospheric Sounding – STRatospheric aircraft) observations in the spectral regions from 725 to 990 and 1150 to 1350 cm−1 under conditions suitable for the existence of nitric acid trihydrate (NAT) above northern Scandinavia on 11 December 2011. The high-resolution infrared limb emission spectra of MIPAS-STR show a characteristic “shoulder-like” signature in the spectral region around 820… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…The morphology of NAT particles is still an open question, as is the compactness of the particles Woiwode et al, 2014Woiwode et al, , 2016. Light scattering studies have repeatedly shown that detailed particle morphology cannot be deduced from the depolarization; e.g., Nousiainen et al (2012) investigated simple and complex shapes with size parameters (ratio of the particle circumference to the wavelength) in the range 2-12 and real refractive indices in the range 1.55-1.603 representative of silicate particles, and noted similar depolarization ranges for the fifteen different shapes (regular and irregular) that were analyzed.…”
Section: Sts/nat Mixturesmentioning
confidence: 99%
“…The morphology of NAT particles is still an open question, as is the compactness of the particles Woiwode et al, 2014Woiwode et al, , 2016. Light scattering studies have repeatedly shown that detailed particle morphology cannot be deduced from the depolarization; e.g., Nousiainen et al (2012) investigated simple and complex shapes with size parameters (ratio of the particle circumference to the wavelength) in the range 2-12 and real refractive indices in the range 1.55-1.603 representative of silicate particles, and noted similar depolarization ranges for the fifteen different shapes (regular and irregular) that were analyzed.…”
Section: Sts/nat Mixturesmentioning
confidence: 99%
“…In addition combined lidar or in-situ observations from aircraft (e.g. Fahey et al, 2001;Northway et al, 2002) could help to answer the question on the abundance of the upper NAT branch, which might include aspherical NAT particles as observed by Molleker et al (2014) and Woiwode et al (2016). Generally this branch is of importance for denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…As a rough estimate, a 10-µm sized ice crystal sediments about 1 km in a day (Fahey et 10 al., 2001). For aspherical particles the sedimentation rates are even lower (Woiwode et al, 2014;Woiwode et al, 2016;Weigel et al, 2014;), hence generally our simplified calculations cover the altitude range of sedimenting PSC particles.…”
Section: Temperature History Of Trajectories Starting In Ice Nat or mentioning
confidence: 99%
“…Simulations of highly aspherical β-NAT particles are based on T-Matrix calculations (Bi et al, 2013) and are used to define the criteria of our method. As in Woiwode et al (2016), we adopt elongated spheroids with an aspect ratio of 0.1. Note that highly oblate spheroids with an aspect ratio of 10 produced similar results in the previous study.…”
Section: New Methods To Detect Large Nat Particlesmentioning
confidence: 99%
“…Ice is likely to play an important role in NAT nucleation (Weiss et al, 2016). While state-of-the-art parameterizations of large NAT particles are successful in reproducing major patterns of denitrification and the state at the end of the winter, large discrepancies remain in direct comparisons with rare Arctic particle field observations (Grooß et al, 2014;Molleker et al, 2014;Woiwode et al, 2016;Zhu et al, 2015). Depending on the different models and scenarios, simulated particle sizes are significantly smaller and/or number densities significantly lower than observed.…”
Section: Introductionmentioning
confidence: 99%